(3GdahGFO GdCUhdjIs - (3GdHgHgGfj, GdCSJGP GdCcHQ, GdhMjO, eMeO HGbQ Hf eMeO Cced, (B1206 (3g`s ((3Ydj Hf cQHdGFj SHMGfhQOjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3aEfg deG HYO GdYgO Yf ReGf GdCFeI hNaj CeGQGJ Gdabg hGdCOdI Ydi eG cGf GdebQQ YfO GdabgGA hGdeYghO Hjfge HdG NaGA HGfbQGVge hNdh GdOjGQ Yfge Edi Cf GfWeS CcKQ BKGQge (B..s
(3BNQgG (B:s
... (3hjefY Yf GdJgPjH Hd hQHeG jhQK GdbSGhI ceG hQO aj GdMOjK aj eYQaI GdfMh hfTGgO aj ZjQgG eY Cf JgPjH GdCNdGb ef ChLH GdCTjGA ceG dG jNai hGddg gh GdgGOjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\49s
(3GdCYdGe (B6\49s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs